Does Black Economic Empowerment Ownership Matter? A Decolonial Analysis of "Black Visibility" in South Africa's Print Media Content, 1994–2014. Issue 2 (3rd April 2022) - Govenden, Prinola
ABSTRACT: Ownership is identified as one of the major factors that influence the production of news. South Africa's print media transformation situation presents an important Global South case study for journalism debates about ownership effects on news. The country's media transformation agenda is based on the premise that transformation of ownership will automatically lead to a transformation of content on these levels. This study empirically examines whether the racial changes in print media ownership facilitated by black economic empowerment in the first 20 years of South Africa's democracy (1994–2014) led to transformation of content with a focus on racial stereotypes of blackness. It conducts a decolonial analysis of the representation of blackness in three issues that have framed post-apartheid South Africa: socioeconomic rights; labour issues and protests; black government vs. big business or "white economic elite". The findings show that despite an increase in black ownership, "inferential racism" of blackness pervades content. The nature of representation also coincides with decolonial theory's concept of "non-being" and its enunciation of the colonised subject being the "damned of the earth", in the near invisibility of black people's struggles, hypervisibility of black leadership shortcomings, and in the depiction of protestors as inherently violent, disorderly, deviants, and criminals. The study concludes that in the case of South Africa ownership does not matter, a change from white ownership to considerable black ownership since 1994 did not significantly "transform" historical racist tropes of blackness in content.